Employee Performance Assessment Based On Competency - Ratna Tri Hari Safariningsih; Hafifuddin Hafifuddin (Economy Deposit Journal (E-DJ), 2022)
Competence at present is the basis for the performance assessment. The primary objective of performance assessments is to optimize team member performance where faith must link team member duties and characteristics to organizational strategy.Performance assessments are done to measure employees' performance objectively and hereafter expected to provide valid performance assessments according to the employees' competence. The research aimed at knowing what competency criteria were judged in team member performance. (SLR) research methods used literature review (SLR) through the vold's help, by applying previous research to find any competence criteria that were used for team member performance assessments. Research results found on the competence criteria for assessed employment performance include the following: 1) commitment to organization, 2) a spirit of achievers, 3) serves, 4) teamwork, 5) proactive, 6) leads, 7) discipline , 8) thinks analytical and 9) self-control. Research results will be made as a recommendation for the performance assessments of employees at the education hospital in Jabodetabek